The Nature of the Atypical Kinetic Effects Observed for the Thermally Induced Spin Transition in Ferrous Nitroprussides with Short Organic Pillars. Issue 24 (11th July 2022) - Avila, Yosuan; Scanda, Karla; Díaz‐Paneque, Luis A.; Cruz‐Santiago, Lorenzo A.; González, Marlene; Reguera, Edilso
Abstract: In pillared 2D ferrous nitroprussides, Fe(L)x [Fe(CN)5 NO] where x=1, 2, and L is an appropriate organic molecule, the axial CN and NO groups are dangling ligands found in the interlayer region. These ligands subtract electron density from the iron atom in the nitroprusside building block via π‐back bonding interaction. That electron density appears accumulated at their CN5σ and NOπ* orbitals, and for the case of short pilar molecules, such electron density is responsible for the appearance of a repulsive force between adjacent layers. In the series of ferrous nitroprussides with short pillar molecules herein considered (L=pyrazine, pyridine, and 4‐methylpyridine), that repulsive electrostatic interaction opposes the unit cell volume contraction during the spin transition (HS→LS) on the sample cooling and it favors the cell expansion that accompanies the inverse spin transition (LS→HS) when the sample is warmed. This results in an atypical kinetic behavior for the thermally induced spin transition in these materials. The lower the scan rate, the greater the shift of the HS→LS transition towards low temperatures. The features of this effect are herein discussed. For a large pillar molecule, e. g . 4, 4'‐azopyridine, or in the absence of that electrostatic interaction, for instance, in Fe(Pyz)[Pt(CN)4 ] where Pyz=pyrazine, such an atypical effect is not observed. The results discussed in this contribution illustrate how relevant could be the structural factors on the spin crossover (SCO) in coordination polymers. This study includes an evaluation of the effects of repeated cycles of cooling and warming on the recorded magnetic data, considering that the spin transitions involve nucleation and growth processes of the solid crystallites and structural changes within the solid framework. Abstract : The atypical kinetic effects in ferrous nitroprussides result from the repulsive electrostatic interactions between the negative charge density located at the N and O ends of the axial CN and NO ligands.